Hardy to Heaney : twentieth century poets : introductions and explanations - Blackburn, John, 1931- (Edinburgh : Oliver & Boyd, 1986)
A collection of essays offering commentary and criticism on the work of "important twentieth-century" English and American poets.
Keywords: English poetry -- 20th century -- History and criticism; American poetry -- 20th century -- History and criticism; English poetry -- 20th century -- History and criticism; American poetry -- 20th century -- History and criticism; English-speaking countries -- Intellectual life -- 20th century